Effect of fish meal source on nursery pig performance - Jones, A. M.; Woodworth, J. C.; Goodband, Robert D.; Tokach, Michael D.; Dritz, Steven S.; DeRouchey, Joel M. (My University, 2016)
A total of 350 pigs (DNA Line 200 × 400; initially 6.5 ± 0.09 kg BW; 21 d of age) were used in a 14-d experiment to determine the effects of fish meal source on nursery pig performance. Pigs were randomly allotted to pens at weaning (d 0) and were fed a common starter diet for 7 d. On d 7, pens of pigs were randomly allotted by BW to 1 of 7 dietary treatments (10 pens/treatment and 5 pigs/pen) in a 2 × 3 + 1 factorial. Diets were corn-soybean meal-based that contained 10% dried whey and none (Control) or 3 or 6% fish meal from 1 of 3 sources (IPC 790 Fish Meal, The Scoular Company, Minneapolis, MN; Special Select Menhaden Fish Meal, Omega Proteins, Houston, TX; and Daybrook LT Prime Menhaden Fish Meal, Daybrook Fisheries, Morristown, NJ). All fish meal sources were from the 2014 catch year. All samples of fish meal contained less than 0.15% total volatile N suggesting high quality. A source × level interaction (P < 0.05) for ADG and final BW was observed as increasing levels of IPC 790 improved ADG; however, pigs fed Special Select and LT Prime fish meal only saw improvement when 3% was included. While no differences were observed between treatments for ADFI, there was a source × level interaction for G:F (Linear P = 0.005). This was a result of G:F linearly improving as IPC 790 increased, with pigs fed 3% Special Select or LT Prime having similar performance to 6% IPC 790, but no further improvement thereafter. In conclusion, adding 3% of any fish meal source improved ADG and G:F; however, only pigs fed IPC 790 had a further improvement in ADG when 6% was fed.
Citation: Jones, A. M., Woodworth, J. C., Goodband, R. D., Tokach, M. D., Dritz, S. S., & DeRouchey, J. M. (2016). Effect of fish meal source on nursery pig performance. Journal of Animal Science, 94, 94-94. doi:10.2527/msasas2016-199
Keywords: Fish Meal; Growth; Nursery Pig; Agriculture